O sombrio na xilogravura: um diálogo com o expressionismo de Goeldi - Silveira, Márcio Rogério Silveira da (My University, 2024)
This monograph is the result of research carried out during the Course Completion Work (TCC) of the Bachelor of Visual Arts with the aim of presenting an authorial production of woodcuts. A relationship is established with German expressionism, considering the influence of this period of art on Brazilian engraving. The work presented here has as its main reference the work of Oswaldo Goeldi, a fundamental artist in this study to achieve the dark in woodcuts. Thus, based on bibliographical research, the study of woodcuts in the context of art, considering the involvement of Brazilian artists with the technique, influenced by expressionism, the author deepens his investigation into Goeldi's woodcut work and establishes relationships with artistic production, culminating in the series composed of woodcuts: "The boat"; "Moon"; "What do you laugh at?"; "Tunnel light: Beginning or end?"; "Loneliness" and "Cemitery crime", exhibited at the Arts Gallery of Campus 8 of the University of Caxias do Sul (UCS). [resumo fornecido pelo autor]
Esta monografia é resultado da pesquisa realizada durante o Trabalho de Conclusão do Curso (TCC) de Bacharelado em Artes Visuais com o objetivo de apresentar uma produção autoral de xilogravuras. Se estabelece uma relação com o Expressionismo alemão, considerando a influência deste período da arte para a gravura brasileira. O trabalho, ora apresentado, tem como principal referência a obra de Oswaldo Goeldi, artista fundamental neste estudo para se chegar ao sombrio na xilogravura. Desse modo, a partir de uma pesquisa bibliográfica, do estudo da xilogravura no contexto da arte, considerando o envolvimento de artistas brasileiros com a técnica, influenciados pelo Expressionismo, o autor aprofunda sua investigação na obra xilográfica de Goeldi e estabelece relações com a produção artística, culminando na série composta pelas xilogravuras: "O Barco"; "Lua"; "Do que riem?"; "Luz do túnel: Início ou fim"; "Solidão" e "Crime do cemitério", expostas na Galeria de Artes do Campus 8 da Universidade de Caxias do Sul (UCS). [resumo fornecido pelo autor]
Keywords: Artes; Xilogravura; Expressionismo (Arte); Goeldi, Oswaldo, 1895-1961